ANALISIS Z-SCORE DALAM MENGUKUR KINERJA KEUANGAN UNTUK MEMPREDIKSI KEBANGKRUTAN PERUSAHAAN MANUFAKTUR PADA MASA PANDEMI COVID-19 - Kristina Dewanti Setyaningrum; Apriani Dorkas Rambu Atahau; Imanuel Madea Sakti (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2020)
A manufacturing company is a business entity whose main activity is to process raw materials into finished goods, therefore they have a sale value. During the covid-19 pandemic, many manufacturing companies were threatened with bankruptcy. That is because the company’s performance has decreased. The purpose of this research is to compare how big the opportunities of PT. Astra International, PT. Mandom Indonesia, PT. Gudang Garam, and PT. Sri Rejeki Isman bankruptcy as a result of covid-19 by using the Altman z-score model. Financial distress is a situation where a company experiences liquidity difficulties or the ability to fulfill its obligations. Based on the results of PT. Astra International from 2016 to 2020 in the first quarter was potentially bankruptcy, while in the second quarter the company was based on the grey area. PT. Mandom Indonesia both in the first quarter and second quarter in healthy. PT. Gudang Garam in first quarter and second quarter in the grey area. PT. Sri Rejeki Isman in the first quarter and second quarter classified as a potentially bankrupt company.